Assessing and addressing missed opportunities for vaccination in Cape Town through a collaborative quality improvement approach - Nnaji, Chukwudi (Department of Public Health and Family Medicine, 2024)
Background: While significant investments and efforts have been made to promote universal access to immunisation services in South Africa, current evidence shows substantial coverage gaps across the country. Missed opportunities for vaccination (MOV) have been recognised as a major contributor to sub-optimal immunisation coverage globally. The overall aim of the research and its component studies was to assess and address MOV in primary health care (PHC) settings in Cape Town. To achieve this overarching goal, the research sought to address five specific objectives. It started with quantitative and qualitative assessments of the magnitude and multi-dimensional factors associated with MOV among children aged 0-23 months attending PHC facilities in the Cape Town Metro Health District. The goal of that formative assessment was to help inform the design, implementation and evaluation of contextually appropriate quality improvement interventions targeted at reducing MOV in participating PHC facilities. In addition, the research sought to contribute important evidence on the feasibility, effectiveness and sustainability of quality improvement interventions in addressing MOV in PHC contexts. Study rationale, supporting literature and specific objectives are described in detail in Chapters 1-2. Methods: The research used a mixed-methods approach, incorporating data from both quantitative and theory-informed qualitative studies. To address the five specific objectives, the research had five component studies. The first study involved a quantitative assessment of the magnitude of MOV and associated factors (Chapter 3), consolidated with two qualitative studies to provide deeper understanding and contextualisation of the first study's quantitative findings from the perspectives of caregivers and health workers (Chapter 4). These were followed by a non-randomised controlled study to evaluate the effectiveness of the package of quality improvement strategies implemented in participating health facilities (Chapter 5) and a post-intervention mixed-methods evaluation of the factors facilitating or hindering the successful implementation of quality improvement interventions (Chapter 6). Study design, methodological considerations and conceptual underpinnings are described in detail in various study chapters (Chapters 3-6). Strengths and limitations of each study design are also discussed in their respective chapters, as are their implications for further research. Results: The first component study (reported and discussed in detail in Chapter 3) involved a quantitative study that aimed to assess the prevalence and determinants of MOV in PHC settings in Cape Town. It found a prevalence of 14% and identified individual and health system factors associated with MOV. The second study (reported and discussed in Chapter 4) used a qualitative design (focus group discussions with caregivers) to explore the factors that may influence MOV among children in the study setting. Similarly, the third study (reported also in Chapter 4) employed another qualitative design (in-depth interviews) to explore the factors that may influence MOV from the perspectives of healthcare workers. Both qualitative studies provided important contextual insights that complemented and enhanced understanding of the findings from the quantitative MOV assessment. In the fourth component study (reported and discussed in Chapter 5), findings from the quantitative and qualitative baseline assessments were used to design and evaluate a package of facility-level quality improvement interventions. From the evaluation using a non-randomised controlled design, we found that implementing contextually appropriate quality improvement strategies was feasible and effective at reducing MOV occurrence in participating PHC facilities. In the final study, we used a mixed-methods evaluation design to conduct a post-implementation evaluation of the quality improvement intervention. From that, we were able to identify the quality improvement implementation facilitators and barriers and how they influenced participants' experiences and perceptions of implementation outcomes, the understanding of which is important for informing the adaptation and sustainability of future MOV-targeted quality improvement strategies. Conclusion Overall, the research has demonstrated that there was a substantial burden of MOV among children in Cape Town. It has also provided some scientifically robust evidence on the feasibility, effectiveness and adaptability of a facility-level quality improvement intervention for addressing MOV in primary health care contexts in Cape Town and similar contexts. Implications of study findings for policy, practice and further research have been discussed with specific recommendations in various study chapters (Chapters 3-6) and consolidated in the integrated discussion in the final chapter (Chapter 7).